The Benefits of Blockchain Technology for Medical Tourism - Tyan, Inessa; Guevara-Plaza, Antonio; Yague-Valle, María Inmaculada (MDPI, 2021)
The paper discusses the benefits of blockchain technology for medical tourism. The major focus is placed on pre-procedure and post-procedure of medical tourism. The authors argue that blockchain technology can facilitate several stages of medical tourism by enabling disintermediation, allowing cryptocurrency payments, ensuring secure data sharing and privacy, and empowering trusted review systems. With regard to COVID-19 pandemic, the paper outlines the current challenges of the medical tourism industry and prop oses the opportunities for blockchain technology use. The paper attempts to provide important insights regarding the positive implications of blockchain technology use within the medical tourism industry as well as to further advance the current knowledge about blockchain technology’s effects for medical tourism.
Keywords: Asistencia sanitaria; Blockchain; Medical tourism